A novel hybrid control strategy for potential energy regeneration systems of hybrid hydraulic excavators. (May 2016) - Chen, Qihuai; Wang, Qingfeng; Wang, Tao
Excavators as a kind of typical construction machinery are widely used in all kinds of earthworks. Due to the low efficiency of the excavator, many enterprises and researchers have been committed to improving its efficiency. Energy regeneration system is an effective energy-saving technology, which has attracted much attention in recent years. However, the traditional energy regeneration system pays much attention to the energy saving, while the maneuverability is not fully considered. This article focuses on the maneuverability and the energy saving of the hybrid hydraulic excavator boom. A novel hybrid control method to guarantee the dynamic performance of the energy regeneration system, which is based on an electrical potential energy regeneration system, is proposed. A combined use of a torque controller for the permanent-magnet synchronous machine and a position controller for the proportional pressure valve makes the dynamic performance of the potential energy regeneration system insensitive to the influence from the direct current voltage, the capacity of the inverter as well as the cylinder speed, and achieves fast response and maximum energy regeneration simultaneously. To verify the effectiveness of the hybrid control method for the potential energy regeneration system, co-simulations are carried out in AMESim and Simulink. The results show that the dynamic performance of the potential energy regeneration system with the hybrid control method is close to a throttle-governing system and the regenerated potential energy is considerable.